Biogeochemistry of macrophytes, sediments and porewaters in thermokarst lakes of permafrost peatlands, western Siberia - Manasypov, Rinat M.; Pokrovsky, Oleg S.; Shirokova, Liudmila S.; Auda, Yves; Zinner, Nadezhda S.; Vorobyev, Sergey N. (биолог); Kirpotin, Sergey N. (Science of The Total Environment, 2021)
The chemical composition of thermokarst lake ecosystem components is a crucial indicator of current climate change and permafrost thaw. Despite high importance of macrophytes in shallow permafrost thaw lakes for control of major and trace nutrients in lake water, the trace element (TE) partitioning between macrophytes and lake water and sediments in the permafrost regions remains virtually unknown. Here we sampled dominant macrophytes in thermokarst lakes of discontinuous and continuous permafrost zones in the Western Siberia Lowland (WSL) and measured major and trace elements in plant biomass, lake water, lake sediments and sediment porewater. All six plant species (Hippuris vulgaris L., Glyceria maxima (Hartm.) Holmb., Comarum palustre L., Ranunculus spitzbergensis Hadac, Carex aquatilis Wahlenb s. str., Menyanthes trifoliata L.) sizably accumulated macronutrients (Na, Mg, Ca), micronutrients (B, Mo, Nu, Cu, Zn, Co) and toxicants (As, Cd). Accumulation of other trace elements, including rare earth elements (REE), in macrophytes relative to pore waters and sediments was highly variable among species. Using miltiparametric statistics, we described the behavior of ТЕ across two permafrost zones and identified several group of elements depending on their sources in the lake ecosystems and their affinity to sediments and macrophytes. Under future climate warming and shifting the permafrost border to the north, we anticipate an increasing uptake of heavy metals and lithogenic low mobile elements such as Ti, Al, Cr, As, Cu, Fe, Ni, Ga, Zr, and REEs by macrophytes in the discontinuous permafrost zone and Ba, Zn, Pb and Cd in the continuous permafrost zone. This may eventually diminish transport of metal micronutrients and geochemical tracers from soils to lakes and rivers and further to the Arctic